A New Finding on the Enhancement of the Ability of Polysulfide Adsorption of V2O5 by Doping Tungsten in Lithium–Sulfur Batteries. Issue 12 (7th June 2019) - Gao, Feng; Yan, Xinxiu; Li, Xuan; Qiao, Yingjun; Shang, Huimin; Zhang, Yanhua; Fan, Weifeng
Abstract : Lithium–sulfur batteries are considered to be the most commercially promising lithium metal secondary batteries due to their high specific capacity. However, the shuttle effect of lithium polysulfide (LiPS) in the electrolyte seriously hinders the development of lithium–sulfur batteries. W‐doped V2 O5 (W‐V2 O5 ) is prepared by a hydrothermal method, which greatly improves the LiPS adsorption ability of V2 O5 . The W‐V2 O5 powder can discolor the LiPS solution in 1 min. Then, W‐V2 O5 is combined with a graphene/carbon nanotube composite (G/CNT) with good conductivity to modify the separator. As a result, the W‐V2 O5 ‐G/CNT‐coated separator allows the sulfur cathode to reach a high initial discharge capacity of 1200 mAh g −1 at 0.2 C and a reversible capacity of 815 mAh g −1 after 200 cycles at 0.5 C, and leads to an excellent rate ability (up to 2 C rate) and a high coulombic efficiency of 99.5%. This provides a new direction for designing efficient LiPS catalysts. Abstract : W 6+ ‐doped V2 O5 can greatly enhance the adsorption speed of V2 O5 for lithium polysulfide (LiPS), which makes a red LiPS solution fade in 1 min. The metal oxide is mixed with the graphene/carbon nanotube composite to modify the separator, which can greatly improve the cycle performance of the lithium–sulfur battery.